The Candidate Photoperiod Gene MtFE Promotes Growth and Flowering in Medicago truncatula - Thomson, Geoffrey; Zhang, Lulu; Wen, Jiangqi; Mysore, Kirankumar S.; Putterill, Joanna (Frontiers in Plant Science, 2021)
Flowering time influences the yield and productivity of legume crops. Medicago truncatula is a reference temperate legume that, like winter annual varieties of Arabidopsis thaliana, shows accelerated flowering in response to vernalisation (extended exposure to cold) and long day (LD) photoperiods (VLD). However, unlike A. thaliana, M. truncatula lacks homologues of core flowering time regulators CO and FLC which act upstream of the mobile florigen FT. Temperate legumes like pea and M. truncatula have three LD induced FT-like genes. MtFTa1 promotes M. truncatula flowering in response to VLD. The FE gene is another candidate element of the photoperiod pathway, but has not yet been studied outside A. thaliana. FE acts to induce FT expression and regulates the FT transport pathway. It is also required for phloem development. Our study identifies a broadly expressed homologue of FE in M. truncatula, Medtr6g444980 (MtFE). MtFE complements the late flowering fe-1 A. thaliana mutant when expressed from the phloem specific SUCROSE TRANSPORT PROTEIN 2 promoter. Analysis of two M. truncatula Tnt1 retroelement insertional mutants indicate that MtFE promotes flowering in LD and VLD. It also promotes growth in all conditions tested. Expression of MtFTa1, MtFTb1 and MtFTb2 are reduced in Mtfe mutant (NF5076), correlating with the delayed flowering observed in this mutant. The NF5076 Mtfe mutant plants are much smaller than wild type plants indicating that MtFE is important for normal plant growth. The second mutant (NF18291) displays seedling lethality, similar to strong Atfe mutants. An allelic cross flowers late like the NF5076 Mtfe mutant. We also searched for mutants in MtFTb1 and MtFTb2 and identified a Mtftb2 knock out Tnt1 mutant (NF20803). However, it did not flower significantly later than wild type. Previously, yeast-two-hybrid assays (Y2H) suggested that Arabidopsis FE interacted with CO and NF-Y-like proteins to regulate FT. Here, we found that MtFE interacts with Arabidopsis CO and also M. truncatula NF-Y-like proteins in Y2H experiments. Our study reveals that despite the absence of a functional CO, M. truncatula FE nevertheless influences photoperiodic FT expression and flowering time in M. truncatula via a partially conserved mechanism with A. thaliana.